Answer:
4⋅(−9)⋅(−3)⋅(−1) product is negative,
Step-by-step explanation:
Given : Numbers .
To find : Which product is negative.
Solution : We have given expression with positive sign and negative sign.
By the integer rule : When we multiplied the even number of negative it become positive .
Example: -a * - b = ab.
When we multiplied the odd number of negative it become negative .
Example: -a * - b* -c = - abc.
This expression have −6⋅(−7)⋅(−8)⋅0 have 3 negative sign but it has 0 so, this expression would be zero.
Then only this 4⋅(−9)⋅(−3)⋅(−1) expression have 3 negative sign
So, its product would be negative.
Therefore, 4⋅(−9)⋅(−3)⋅(−1) product is negative,
The negative answer is the last one, 4⋅(−9)⋅(−3)⋅(−1)
positive times a negative = a negative
negative times a negative= a positive
a positive times a negative= a negative
To be able to graph this you need to start on -2 on the y-axis then move up 5 then 1 to the right
The dot should be on (1,3)
Answer: 50
Step-by-step explanation: The equation of Celsius to Fahrenheit is multiply by 1.8 (or 9/5) and add 32.
Answer:
The key features of any function can be compared in tables and graphs by creating the matching graph for the function. Then, you can compare the different aspects of the graph. When you add a constant to an exponential graph, it will be translated up or down.
hopethishelps......
Answer:
ion kno t f
Step-by-step explanation:
Answer:
A lies on (1,3) a reflection across the y-axis is (x,y) to (-x,y). The x turns the opposite and y stays the same so...
(-1,3)
Answer:
Ok, I'm not the smartest but I think the first one D 2nd = 6,-2 3rd is B 4th= D
and the 5th C
Answer:
Step-by-step explanation:
good
Answer:
The correct answer is,
(x + 3)² + (y +1)² = 25
Step-by-step explanation:
It is given that, What is the equation of a circle with center (-3,-1) that contains the point (1,2)
Formula;-
Equation of the circle passing through the point ( x₁,y₁) with radius r is given by,
(x - x₁)² + (y - y₁)² = r²
To find the radius of circle
r =√[ (1 --3)² + (2 --1)²]
=√(4² + 3²)
= √(16 + 9)
=√25 = 5
To find the equation of the circle
(x₁, x₁) = (-3, -1) and r = 5
(x - x₁)² + (y - y₁)² = r²
(x - -3)² + (y - -1)² = 5²
(x + 3)² + (y +1)² = 25
Answer:
(x + 3)^2 + (y + 1)^2 = 25
Step-by-step explanation:
Equation of a circle with center (h, k) and radius, r.
(x - h)^2 + (y - k)^2 = r^2
The center is (-3, -1), so h = 1, and k = 2.
(x - (-3))^2 + (y - (-1))^2 = r^2
(x + 3)^2 + (y + 1)^2 = r^2
Now we substitute x and y with the values of x and y from the given point, and we solve for r^2.
(1 + 3)^2 + (2 + 1)^2 = r^2
4^2 + 3^2 = r^2
16 + 9 = r^2
r^2 = 25
Now that we know r^2, we substitute it into the equation above.
(x + 3)^2 + (y + 1)^2 = 25